CONTENT MARKETING STRATEGY IN INCREASING CONSUMER INTERACTION ON SOCIAL MEDIA - Popo Suryana (Sean Institute, 2022)
This research aims to investigate and analyze content marketing strategies that are effective in increasing consumer interaction on social media platforms. This research uses a qualitative approach with descriptive methods. The research results show that implementing a content marketing strategy with a focus on quality, engagement and consumer interaction on social media has a positive impact. Through data analysis and campaign performance monitoring, we can see increased brand awareness, strong relationships with audiences, and an active online community. Fast response to consumer interactions and utilization of social media analytics tools help companies measure and improve the effectiveness of their content marketing strategies. These results underscore the importance of optimizing content marketing in the digital era to build meaningful connections with consumers, gain trust and strengthen a brand's position in the world of social media.